Horse drawn cart hauling lumber stuck in mud on Front St., Dawson, Yukon Territory, approximately 1899. - Hegg, Eric A., 1867-1948 (1899)
Shows "The Dominion" and "Arcade Restaurant" in background Caption on image: "(Front Street) Dawson Main Street 1898" Original photograph by Eric A. Hegg 3094; copied by Larss and Duclos. No. 33 appears in lower left corner. Klondike Gold Rush.